PERAN PUTRI BAYAN DALAM PROSES ISLAMISASI LOMBOK: ANALISIS BERBASIS NASKAH BABAD LOMBOK - Haekal Ghifari; Pepep Ipan Sopian; Dedi Supriadi; Asep Achmad Hidayat; Syahidah Qolbiya Sakinah; Yan Nurcahya (Jazirah: Jurnal Peradaban dan Kebudayaan, 2026)
Traditional historiography such as Babad Lombok contains many cultures, one of which is about women. Babad Lombok contains the genealogy of the Prophet, the Menak in Lombok, and Islamization in Lombok. Through a philological and hermeneutic approach, the interpretation of Babad Lombok is mainly through the perspective of Muslim women. Islamization which was first carried out by Sunan Prapen made the Lombok Kingdom an Islamic Kingdom. Islam or not is shown through women who embrace Islam or not in this region. As a result of the women who did not convert to Islam, there was a war between Sunan Prapen and the Lombok community who had not embraced Islam until finally Lombok was divided into three parts. Furthermore, Islamization was carried out by Rangkesari as the king of Selaparang. Furthermore, Selaparang was made the capital of the Lombok Kingdom which had embraced Islam. Prabu Anom, Rangkesari's successor, made the Selaparang Kingdom in this case Lombok reach the peak of its glory. Princess Bayan became the person behind the glory carried out by Prabu Anom by doing good deeds by accepting polygamy carried out by her husband. Good deeds were carried out after there was a policy within oneself. This acceptance uses faith with knowledge so that the evidence speaks of the virtues he carried out for the Islamization carried out in the Kingdom of Lombok in the glory days of his time.